Trends in Antibiotic Use in Danish, Finnish, Norwegian and Swedish Children - Skajaa N; Gehrt L; Nieminen H; Laake I; Englund H; Sönksen UW; Feiring B; Benn CS; Trogstad L; Palmu AA; Sørup S (Clinical Epidemiology, 2022)
Nils Skajaa,1– 4 Lise Gehrt,3,4 Heta Nieminen,5 Ida Laake,6 Hélène Englund,7 Ute Wolff Sönksen,8 Berit Feiring,6 Christine Stabell Benn,3,4,9 Lill Trogstad,6 Arto A Palmu,5 Signe Sørup1,3 1Department of Clinical Epidemiology, Aarhus University Hospital, Aarhus, Denmark; 2National Institute of Public Health, University of Southern Denmark, Copenhagen, Denmark; 3Research Center for Vitamins and Vaccines, Statens Serum Institut, Copenhagen, Denmark; 4Bandim Health Project, Open Patient Data Explorative Network, Odense University Hospital/Department of Clinical Research, University of Southern Denmark, Odense C, Denmark; 5Department of Public Health and Welfare, Finnish Institute for Health and Welfare, Tampere, Finland; 6Division of Infection Control and Environmental Health, The Norwegian Institute of Public Health, Oslo, Norway; 7Unit for Vaccination Programmes, Public Health Agency of Sweden, Solna, Sweden; 8Reference Laboratory for Antimicrobial Resistance, Infection Preparedness, Statens Serum Institut, Copenhagen, Denmark; 9Danish Institute for Advanced Study, University of Southern Denmark, Odense C, DenmarkCorrespondence: Signe Sørup, Department of Clinical Epidemiology, Aarhus University Hospital, Olof Palmes Allé 43-45, Aarhus N, 8200, Denmark, Email SigneSorup@clin.au.dkObjective: To compare the use of antibiotics in children in four Northern European countries.Methods: We conducted a register-based study based on individual-level prescription data from national prescription registers. We identified all redeemed outpatient prescriptions for systemic antibiotics in children aged 0– 14 years from July 2006 to June 2017 in Denmark, Finland, Norway, and Sweden. We computed incidence rates and incidence rate ratios of treatment episodes with any antibiotic and different antibiotic classes.Results: In 2016/2017, the rates of antibiotic treatment episodes per 1000 person-years in children aged 0– 14 years were 429, 284, 219, and 184 in Finland, Denmark, Sweden, and Norway, respectively, and the rate ratios (95% confidence intervals) compared with Norway were 2.33 (2.33– 2.34), 1.54 (1.54– 1.55), and 1.19 (1.19– 1.20) in Finland, Denmark, and Sweden, respectively. The rate of antibiotic treatment episodes declined over time in all countries. The relative reductions in 2016/2017 compared with 2006/2007 were 36% in Finland, 40% in Denmark, 49% in Sweden, and 29% in Norway. Treatment episodes peaked between age 12 and 18 months. The most used antibiotic class was beta-lactamase sensitive penicillins among all children in Norway and Sweden and among children above two years in Denmark, while penicillins with extended spectrum were most used in Finland and among the youngest children in Denmark.Conclusion: In all countries, the use of antibiotics in children declined between 2006 and 2017. However, there were still considerable differences in antibiotic use between otherwise quite similar Nordic countries, with a more than 2-fold difference between the countries with the lowest and highest rates. Interventions to reduce the number of antibiotic treatment episodes in the countries with higher rates could reduce the total antibiotic use.Keywords: antibiotic use, pediatric, multi-national comparison, antimicrobial consumption, prescription patterns